An object-oriented method for domain decomposition - Kopysso, S.P.; Krasnoperov, I.V.; Rychkov, V.N. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2003)
An object-oriented model for the domain decomposition method is developed. Based on inheritance, polymorphism, and encapsulation, this model allows one to perform numerical experiments with new decomposition algorithms: to use various schemes of domain decomposition, techniques for storage of systems of equations, methods for their solution, and variants of boundary conditions.